Prevalence of Halitosis Among General Population: A Cross Sectional Study in Jamshoro - Maham Shah, Muneer Ahmed Banglani, Huma Shah, Shahzia Rajper , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To find out the prevalence of halitosis among general population in Jamshoro. Study Design: Descriptive, cross sectional study. Place & Duration: Department of Dentistry, Liaquat University of Medical and Health Sciences Jamshoro, on Marchl9th and 20th 2015. Material & Methods: Two hundred subjects were examined in a free camp and questionnaires were filled by patients who were free from respiratory tract infections. Results: Total subjects included in the study were 200. Gender distribution showed 105 (52.5%) men and 95 (47.5%) women; so, there were more men than women. Moreover, frequency of bad breath showed that 57.9% of women and 33.3070 ofmert were affected from halitosis. Conclusion: Tooth brushing along with tongue brushing should be a part of our daily routine habit. Government and health care professionals should pay more attention on awareness and knowledge of halitosis because halitosis could be a sign of underlying systemic disease.